A growing issue of overuse injuries in young athletes - Trojner, Teodor; Kelc, Robi (Annales Kinesiologiae, 2024)
Over the past two decades, participation in professional sports among children and adolescents has surged despite the rising inactivity and obesity rates. Approximately 60 million young individuals in the USA are involved in organized sports. This increase has led to a concerning rise in overuse syndromes, which is becoming a primary concern in sports medicine. Our review aims to examine common overuse syndromes in youth athletes and assess risk factors, pathophysiology, and preventive measures. Early sports specialization, societal pressures, and competitive demands lead to repetitive strain injuries. The young musculoskeletal system, though adaptable, is prone to injuries from intense training and insufficient recovery. Prevention advocates against early sports specialization and promotes adequate rest. Diversifying sports, limiting training hours, and a robust support system are recommended to counteract the mental effects of intense specialization. In summary, a holistic approach is needed to address overuse syndromes, emphasizing diversification, education, and a balanced approach to sports.